PERAN KONSULTAN PAJAK, KUALITAS PELAYANAN PAJAK, DAN TINGKAT KEPATUHAN PAJAK TERHADAP PEMENUHAN KEWAJIBAN PERPAJAKAN - Hendrik ES Samosir (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to determine the role of tax consultants, the quality of tax services, and the level of taxpayer compliance in fulfilling tax obligations. The population of this study were individual taxpayers registered with the Directorate General of Taxes. The sample in this study was 70 taxpayers taken using purposive sampling techniques. The data collection method used a questionnaire. Data were analyzed by multiple linear regression using the SPSS 23 program. The results of this study are that tax consultants play a positive role in fulfilling tax obligations. The quality of tax services plays a positive role in fulfilling tax obligations. And the level of taxpayer compliance plays a positive role in fulfilling tax obligations.